2021
DOI: 10.1177/08258597211001596
|View full text |Cite
|
Sign up to set email alerts
|

Index Symptoms and Prognosis Awareness of Patients With Pancreatic Cancer: A Multi-Site Palliative Care Collaborative

Abstract: Background: Pancreatic cancer has a poor 5-year survival and carries significant morbidity. Pain is a commonly studied symptom in pancreatic cancer; however, few studies examine the frequency of multiple patient-reported symptoms. Our aim is to ascertain patient-reported symptom burden at initial consultation with a palliative care provider and compare patient prognostic awareness to provider estimation of prognosis. Methods: Data were extracted from the standardized Quality Data Collection Tool (QDACT). Adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Individual risk perception is also influenced by past experiences and cognitive judgments. Studies have shown that factors like trust in doctors and confidence in treatment effectiveness can impact risk perception [ 38 40 ]. Some qualitative studies [ 31 , 41 ] have revealed that some advanced patients with cancer believe that it inevitably leads to death, resulting in a high level of death risk perception, even if treatment is effective.…”
Section: Discussionmentioning
confidence: 99%
“…Individual risk perception is also influenced by past experiences and cognitive judgments. Studies have shown that factors like trust in doctors and confidence in treatment effectiveness can impact risk perception [ 38 40 ]. Some qualitative studies [ 31 , 41 ] have revealed that some advanced patients with cancer believe that it inevitably leads to death, resulting in a high level of death risk perception, even if treatment is effective.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features of PC are not significant. PC has many symptoms, including jaundice, back/abdominal pain, loss of appetite, and weight loss (5). Additionally, PC is extremely aggressive, metastatic, and chemotherapy-resistant (6).…”
Section: Introductionmentioning
confidence: 99%